2015
DOI: 10.1111/1471-0528.13753
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pharmacokinetic properties of magnesium sulphate in women with pre‐eclampsia and eclampsia

Abstract: BackgroundThe pharmacokinetic basis of magnesium sulphate (MgSO 4) dosing regimens for eclampsia prophylaxis and treatment is not clearly established.ObjectivesTo review available data on clinical pharmacokinetic properties of MgSO 4 when used for women with pre‐eclampsia and/or eclampsia.Search strategy MEDLINE, EMBASE, CINAHL, POPLINE, Global Health Library and reference lists of eligible studies.Selection criteriaAll study types investigating pharmacokinetic properties of MgSO 4 in women with pre‐eclampsia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
89
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(104 citation statements)
references
References 24 publications
7
89
0
8
Order By: Relevance
“…For example, loss of the patella tendon reflex was reported to occur at concentrations of 3.5 to 5 mmol/L, and alteration in cardiac conduction and possible cardiac arrest may occur at concentrations of >7.5 and 12.5 mmol/L, respectively. 8 Respiratory depression has also been reported at concentrations of approximately 12 mmol/L. Our simulations indicated that the magnesium concentrations of the standard Zuspan and Pritchard regimens were below the safety margin of 3.5 mmol/L.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…For example, loss of the patella tendon reflex was reported to occur at concentrations of 3.5 to 5 mmol/L, and alteration in cardiac conduction and possible cardiac arrest may occur at concentrations of >7.5 and 12.5 mmol/L, respectively. 8 Respiratory depression has also been reported at concentrations of approximately 12 mmol/L. Our simulations indicated that the magnesium concentrations of the standard Zuspan and Pritchard regimens were below the safety margin of 3.5 mmol/L.…”
Section: Discussionmentioning
confidence: 71%
“…4 A serum magnesium concentration of at least 2 mmol/L has generally been cited as the potential minimum therapeutic concentration. 8 However, a systematic review of 28 studies investigating magnesium sulfate in women with preeclampsia and eclampsia concluded that the minimum effective serum magnesium concentration for eclampsia prophylaxis may be lower than 2 mmol/L. 8 Using our model, simulated magnesium profiles for the standard Zuspan and Pritchard regimens demonstrated slightly lower magnesium concentrations, especially for women with higher body weight and lower creatinine.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This may reflect healthcare providers' familiarity with intravenous administration of MgSO 4 and a belief that higher dosage may result in greater clinical efficacy, as previously suggested in some old studies . In the absence of standard dose–exposure studies on minimum effective concentration of MgSO 4 , this variation in clinical practice is likely to persist for some time due to conflicting views on the optimal dosing regimen to prevent eclamptic seizures. The systematic review of small‐scale randomised trials and observational studies on several alternative MgSO 4 regimens in recent years have concluded that there is still insufficient evidence on their benefits to justify their introduction into clinical practice …”
Section: Discussionmentioning
confidence: 96%
“…The pharmacokinetic basis of MgSO4 dosing regimens for eclampsia prophylaxis and treatment is not clearly established . Minimum effective serum magnesium concentrations for eclampsia prophylaxis are lower than the generally accepted therapeutic level …”
Section: Introductionmentioning
confidence: 99%